Woman, Land and Territory in Contemporary Peruvian Art: Madre Nuestra (2018), by Luz Letts - Vergara, Nataly (2023)
Art as a discursive essence can become a means of reflection on our social reality. Madre Nuestra, by the plastic artist Luz Letts (2018), is an example of this, as this work represents an all-powerful woman who sustains the nation and questions gender stereotypes and violence against women in Peru. In turn, she realizes the powerful relationship of this with the land and territory, and it motivates us to think about the mutual support between women to fight the domination towards the female body and towards the natural world. Thus, it proposes the creation of a female collective identity as a force of the nation, a community defense of land and territory in the process of building a more just society. Finally, it outlines the need to rethink our country with an ecoterritorial and ecofeminist twist.